Dilemma of Antemortem and Post-mortem Fracture: A Brief Research - Kumar , V; K, K; Kaushik, R (Journal of Indian Academy of Forensic Medicine, 2022)
The major duties of a medicolegal system in handling deaths falling under its jurisdiction are to determine the cause and manner of death, identify the deceased if unknown, determining the time of death and injury, collecting evidence from the body that can be used to prove or disprove an individual’s guilt or innocence and to confirm or deny the account of how the death occurred, documenting injuries. However, the most important query that is to be solved during autopsy is to designate an injury as either post-mortem or antemortem. Five cases are discussed here to differentiate antemortem and post-mortem injury. There are various permutations and combinations that makes it difficult to designate an injury antemortem. Even when an injury is antemortem, one couldn’t find the properties of it due to the dynamic process of sustaining an injury. Infiltration of blood in the fractured ends of bones is a process that needs time to appear and depends on the severity of injuries sustained over the body. If the process of sustaining the injuries is sudden and there is rupture of greater blood vessels, one cannot find any infiltration of blood in the bony trabeculae on autopsy.